Research on the Combination of Information Technology and Oral English Teaching. Issue 2 (October 2020) - Ji, Fan
Abstract: The extensive application of information technology, the development of educational resources, the optimization of educational processes, and the improvement of education quality and efficiency in the field of education are the original driving force of education informatization, the promotion of education reform and development, and the cultivation of innovative talents that meet the requirements of the information society. Promote the foundation and premise of educational modernization. With the rapid development of social economy and culture, the integration of information technology in vocational English teaching has become the mainstream. Based on the problems faced by current oral English teaching, this paper explores the possibility of integrating information technology teaching in teaching and the places that need attention, and hopes to provide innovative countermeasures for vocational English teaching.